The language of behaviour changes in dementia: A mixed methods survey exploring the perspectives of people with dementia. (16th February 2021) - Wolverson, Emma; Dunn, Rosie; Moniz‐Cook, Esme; Gove, Dianne; Diaz‐Ponce, Ana
Abstract: Aims: The aim of this study was to explore the opinions of people with dementia, about the language used to describe changes in behaviour associated with dementia. Design: This study adopted a human rights approach in a mixed methods convergent parallel synthesis design. Methods: Online and paper‐based questionnaire data were collected between November 2019 and March 2020. A combination of convenience and purposive sampling was used to invite people with dementia to participate. Results: In total, 54 people completed the survey. There was no clear consensus on a preferred term, but 28.3% preferred the term 'unmet needs' for describing changes in behaviour associated with dementia. Qualitative data revealed important nuances and challenges for researchers and practitioners in relation to terminology for this paradigm. Participants felt that the language we use to talk about changes in behaviour could influence how people with dementia are viewed and treated and how people feel about themselves. Conclusion: The majority of participants were familiar with a range of terminology. There was no universal agreement on terminology, but there was an overall preference for terms that reflect the unmet needs likely to underlie perceived changes in behaviour. Impact: People with dementia raised concerns about the language used to describe changes in behaviour that can occur in dementia. There is scope for improvements in the language used for this paradigm in both research and practice. Following a diagnosis of dementia, clinicians need to take the time to explore an individual's preferences and understandings. They can then share their own understanding about the potential for changed behaviour and if relevant, how any negative impact of this may be minimized. 摘要: 目的: 本研究旨在探讨痴呆症患者对描述痴呆症相关行为变化的语言的看法。 设计: 本研究综合采用人权法和混合法, 并行收敛, 进行综合设计。 方法: 线上和纸质问卷数据收集于2019年11月至2020年3月。采用简便抽样和有目的抽样相结合的方法, 邀请痴呆症患者参与。 结果: 总计54人完成调查。目前, 无明确共识, 但28.3%的人员倾向于用术语"未满足需求"来描述痴呆症相关行为的改变。定性数据可反映研究人员和实践者在这一术语方面的重要、细微差异和所面临的挑战。参与者认为, 尽管我们是用语言来谈论行为变化, 但语言同样可能影响人们对痴呆症的看法、痴呆症治疗以及人们对自身的看法。 结论: 大多数参与者都熟悉术语内容。参与者并未就术语达成一致意见, 但总体上倾向于应用反映未满足需求的术语, 据此反映行为变化。 影响: 痴呆症患者高度关注描述痴呆症相关行为变化的语言。研究和实践过程中, 本范例所用语言有待改进。如果个体已诊断患有痴呆症, 临床医师需要花费时间来探索该个体的偏好和理解。随后, 其可共享自身对行为变更可能性的理解, 如果相关, 应分析如何将其负面影响降至最低。